Bioaumentação em reatores anaeróbio e aeróbio e uso de reator nitrificante para redução da carga orgânica e nitrogenada - Cardoso, Manuela Gomes (2012)
Agro-industrial effluents are capable of causing great impact on water bodies if released without adequate treatment. The removal of the organic load in the conventional biological treatments is achieved with high generation of sludge and energy consumption. The usual techniques of biological removal of nitrogen load demand high deployment and maintenance costs in wastewater treatment units. Seeking the development of a technology that can be employed in treatment units already in operation without high costs of installation and operation, an anaerobic and aerobic reactor using the technique of bioaugmentation and a fixed bed reactor for nitrification were built in scalebench. Real effluent was collected from a meat packing company and microorganisms of high rate of consumption for bioaugmentation were purchased commercially. The biological system was operated continuously with the anaerobic and aerobic reactor in sequence and with recirculation of supernatant from the anaerobic reactor to the nitrifying one. After percolating in the nitrifying reactor, the supernatant was drained back to the bottom of the anaerobic reactor, so that came in contact with the clay formed the bottom of it, making possible the denitrification of nitrogen compounds. Assays were performed under two conditions of flow rate: 2.5 and 5.0 L/day, resulting in organic loading conditions (COA) corresponding to 3.7 and 19.6 gDQOsolúvel/day under constant temperature of 30°C. The anaerobic reactor was evaluated at temperatures of 20 and 30ºC. The nitrification system was tested only for 19.6 gDQOsolúvel/day condition of load. The variations of chemical oxygen demand (COD), soluble COD, NH3, turbidity and suspended solids in each reactor and in the whole system were analized. Were obtained removal of 76.9% soluble COD in the system to the condition of lower COA and 71.1% to 19.6 gDQOsolúvel/day. The microorganisms tested presented solids generation rate (μ) from 0.035 to 0.19 gSSV/gSSV*day, these values are about 10 times lower than those reported for systems without bioaugmentation. The coefficients of biomass growth (Y) and maximum specific substrate consumption (k) were close to those systems without use of the bioaugmentation, indicating that the main advantage of this technique is the lower generation of sludge. It was found that the anaerobic system with bioaugmentation is more resistant to temperature changes compared to the usual system as to reduce the temperature 10°C, there was a reduction of only 27.6% for COD removal. The removal efficiency of NH3 in the system before and after use of the nitrifying reactor was 38.8 and 62%, respectively, indicating that binding of recirculation of the supernatant of the anaerobic reactor to a nitrification reactor designed specifically to allow removing the ammonia load in the effluent.